2014
DOI: 10.1080/14685248.2014.897710
|View full text |Cite
|
Sign up to set email alerts
|

Preferential concentration of heavy particles in turbulence

Abstract: Particle-laden flows are of relevant interest in many industrial and natural systems. When the carrier flow is turbulent, a striking feature is the phenomenon called preferential concentration: particles denser than the fluid have the tendency to inhomogeneously distribute in space, forming clusters and depleted regions. We present an investigation of clustering of small water droplets in homogeneous and isotropic active-grid-generated turbulence. We investigate the effect of Reynolds number (Rλ) and Stokes nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
100
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(132 citation statements)
references
References 19 publications
30
100
2
Order By: Relevance
“…The results show that cluster sizes are distributed over a wide range of scales, from the dissipation up to integral range scales. In agreement with previous studies ( [20,27,30,32,52]), we find that the right hand side of the PDF is well described as a power law with exponent −2, which implies self-similarity of the clusters, in line with results in [20,55]. This slope was found to be ∼ −5/3 in the experimental study of [28].…”
Section: Local Analysis Of Particle Accelerationssupporting
confidence: 92%
See 1 more Smart Citation
“…The results show that cluster sizes are distributed over a wide range of scales, from the dissipation up to integral range scales. In agreement with previous studies ( [20,27,30,32,52]), we find that the right hand side of the PDF is well described as a power law with exponent −2, which implies self-similarity of the clusters, in line with results in [20,55]. This slope was found to be ∼ −5/3 in the experimental study of [28].…”
Section: Local Analysis Of Particle Accelerationssupporting
confidence: 92%
“…These points are often used to define thresholds for detecting clusters and voids, with volumes less than ϑ C denoting clustered regions, and volumes greater than ϑ v denoting void regions. In view of these definitions, it is then apparent that the R λ dependence of the s. In a number of previous studies it has been reported that the PDF of Voronoï volumes follows a log-normal distribution [20,25,27,28,31]. In figure 4 the centered and normalized…”
Section: A Voronoï Volume Distributionsmentioning
confidence: 97%
“…This recurrent question has been considered so far by randomly removing particles from arXiv:1907.07607v1 [physics.flu-dyn] 17 Jul 2019 the collected sets, either from experiments or from numerical data sets. It was shown in [6,7,9] that the Voronoï analysis of clustering is weakly sensitive to sub-sampling. More specifically, relative Voronoï area PDFs and cluster area PDFs are nearly unchanged even if half of the particles present in the original set is randomly removed [6].…”
Section: Introductionmentioning
confidence: 99%
“…For particles having St < 1 clustering is reduced compared to no-gravity case whereas for particles having St > 1 clustering is significantly increased compared to no-gravity case. In a real experiment, gravity is always present hence, these results can be used to understand the experimental observation of particle clustering in turbulent flows [25][26][27].…”
Section: Introductionmentioning
confidence: 99%